Inclusive Teaching and Learning: Strategies to Enhance Inclusivity in Classroom - Sadullaeva Shokhida Bakhodirovna, (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
Classroom is considered as a miniature of society, where diversity can be reflected. Fostering diversity can be founded by inclusive education. Many barriers are faced by learners with special needs while getting knowledge. Traditional measures and strategies could not effectively address difficulties of students with special needs. There is innovative approach is needed which can be solution for problems and challenges, support equality in a wide range of educational institutions.